2018
DOI: 10.1080/14739879.2018.1450096
|View full text |Cite
|
Sign up to set email alerts
|

Continuing education for general practitioners working in rural practice: a review of the literature

Abstract: Background Studies demonstrate that the CME/CPD (continuing medical education/continuing professional development) needs of rural general practitioners (GPs) are unique. Little research has focused specifically on the effectiveness of CME/CPD programmes for rural practice. Aims To review the literature on CME/CPD for GPs in rural areas, focussing on studies which examined impact on doctor performance or patient outcomes. Methods A search of peer-reviewed English language literature and relevant grey literature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 67 publications
0
38
0
Order By: Relevance
“…40 Despite this, a recent review focused on CME for rural GPs concluded that distance learning initiatives did not impact on doctor performance or patient outcomes. 21 This may be due to poor uptake of internet-delivered CME. In a study of an online diabetes educational module, Paul et al found that of 34 (23.3%) GPs who enrolled on the programme, only 8 (5.5 %) completed it.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…40 Despite this, a recent review focused on CME for rural GPs concluded that distance learning initiatives did not impact on doctor performance or patient outcomes. 21 This may be due to poor uptake of internet-delivered CME. In a study of an online diabetes educational module, Paul et al found that of 34 (23.3%) GPs who enrolled on the programme, only 8 (5.5 %) completed it.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…20 What constitutes a 'small group' depends on cultural context, and the terms 'peer review group', 'quality circle', 'CME group', 'practice-based small group work', and 'small group work' are used interchangeably in different European countries. 21 Riley and colleagues 6 reported that GPs who had greater collegial supports feel less isolated, more resilient, and better able to cope with the emotional and clinical demands of their work. A recent Irish study found that GPs who attend CME-SGL may have higher morale and lower stress levels than GPs nationally.…”
Section: Introductionmentioning
confidence: 99%
“…3 Although rural GPs are vital to the availability of primary care in rural areas of developed and developing countries and reportedly have higher CME needs than urban physicians, access to CME can be hampered by the local accessibility; expenses associated with travel, accommodations and participation fees; and increased time off for study. 4,5 The public health policy of China has always put emphasis on rural areas and grassroot communities, 6 as the quality and quantity of GPs are critical to meet the basic medical and public health needs of rural populations. 7 Although rural doctors in China undertake the duties of GPs, some receive no formal training in general practice.…”
Section: Introductionmentioning
confidence: 99%
“…However, despite the strong demand, there is a relative lack of CME resources in rural areas throughout China, as in other countries. 5,9 To address this issue, the aim of the Spring Seedling Project, which is based at the Zhu Shanzhu-Gu Jie Rural Practice Ambulatory Training Center and supported by Fudan University (Shanghai, China), is to integrate social resources to improve accessibility to CME by rural GPs in China. The first program of the Spring Seedling Project was conducted in Zhaotong, a prefecture-level city in Yunnan Province.…”
Section: Introductionmentioning
confidence: 99%
“…13 A review of the literature on continuing medical education/CPD programs for GPs in rural areas found that it was not clear whether these programs improved physician performance and patient care. 14 We have designed a new Family Medicine Brush-up Program, which is an interactive CPD program on primary care aimed at primary care physicians, using a problem-based learning approach. This program is designed to allow participants to learn family medicine through collaborative learning, acquiring the skills needed to practice as a primary care physician and handle the issues that they encounter in their workplaces (Appendix 1).…”
Section: Introductionmentioning
confidence: 99%